2023
DOI: 10.3390/land12050994
|View full text |Cite
|
Sign up to set email alerts
|

Urban Human Settlement Vulnerability Evolution and Mechanisms: The Case of Anhui Province, China

Abstract: In this paper, taking the jurisdiction of Anhui Province as the research area, a vulnerability assessment index system of human settlements was constructed from “exposure–sensitivity–coping ability”. Based on the GIS spatial analysis method, the spatial and temporal evolution characteristics of human settlements in Anhui Province were analyzed. The influences of human factors and natural factors on the spatial differentiation of human settlement vulnerability were explored by using geographic detectors, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Simultaneously, the conversion of high-carbon-density land types (forest and cropland) into low-carbon-density land types (built-up land) has led to a decrease in ecosystem carbon storage service capacity, indicating that LULC still has a negative impact on the ecosystem carbon storage services in the lower reaches of the YRB. Zheng et al [75], Fu et al [76], and Song et al [77] have independently emphasized the significant improvement in urban LULC intensity and the significant expansion of construction areas in the lower reaches of the YRB, including the areas of Shanghai Municipality, Jiangsu Province, and Anhui Province, respectively, following the implementation of the reform and opening up policy. Cai et al [78] have also demonstrated a continuous decline in carbon storage in the Yangtze River Delta region from 1995 to 2020.…”
Section: Ecosystem Service Vulnerabilitymentioning
confidence: 99%
“…Simultaneously, the conversion of high-carbon-density land types (forest and cropland) into low-carbon-density land types (built-up land) has led to a decrease in ecosystem carbon storage service capacity, indicating that LULC still has a negative impact on the ecosystem carbon storage services in the lower reaches of the YRB. Zheng et al [75], Fu et al [76], and Song et al [77] have independently emphasized the significant improvement in urban LULC intensity and the significant expansion of construction areas in the lower reaches of the YRB, including the areas of Shanghai Municipality, Jiangsu Province, and Anhui Province, respectively, following the implementation of the reform and opening up policy. Cai et al [78] have also demonstrated a continuous decline in carbon storage in the Yangtze River Delta region from 1995 to 2020.…”
Section: Ecosystem Service Vulnerabilitymentioning
confidence: 99%
“…It is urgent, then, to improve PPW management to support green agricultural development 9,10 .As important participants in PPW treatment, farmers are the main link for improving its e ciency 11 . China has contractually cooperated with farmers through project-based policies and public service outsourcing to standardize the performance of farmers' duties 12,13 . Although regulations have produced some achievements in PPW treatment, farmers' enthusiasm for PPW participation is generally low 14 , and the recovery rate is less than 15% 15 .…”
Section: Introductionmentioning
confidence: 99%